ANALISIS CITY BRANDING KOTA CIREBON SEBAGAI CULTURE-BASED TOURISM CITY - Ramadhanty, Ghina; Setianti, Yanti; Warta, Waska (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
City branding is a strategy to introduce a city through its advantages. Cirebon City has a city branding with the tagline "The Gate of Secret" which reflects its identity as a culture-based tourist city. This study aims to analyze the implementation of city branding in Cirebon City and formulate strategies that can optimize it. The research method used is qualitative descriptive through observation, interviews, and documentation. The results of the study indicate that the Cirebon City Culture and Tourism Office has implemented various city branding initiatives, such as adding culture-based tourist destinations, making tourist locations a place to work through the Work from Destination (WFD) program, and launching the Wistakon tourism application to facilitate access to information for tourists. However, there are several supporting and inhibiting factors in its implementation. This study provides insight into the importance of overcoming these obstacles to increase the effectiveness of Cirebon City's city branding